Gerakan Bersama Kenali, Cegah dan Atasi Stunting Melalui Edukasi Masyarakat di Desa Cendrana - Resky Devi Akib; Syahriani; Fitriani (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Community service activities are activities carried out in the stunting locus area in Sidrap Regency, which are the service activities and responsibilities of lecturers and students of ITKES Muhammadiyah Sidrap. , 18.8% (2015), 17.8% (2016), and 17.9% (2017). Stunting incidence was 28.9% (2014), 29% (2015), 27.5% (2016), and increased in 2017 by 29.6%. Wasting incidence was 11.8% (2014), 11.9% (2015), 11.1% (2016), and decreased in 2017 by 9.5% (Ministry of Health RI, 2018). The purpose of the service is to increase public knowledge about stunting, so it is necessary to hold a socialization of the Joint Movement to Recognize, Prevent and Overcome Stunting through Community Education in Cendrana Village which is carried out at the Cendrana Village Office, Sidenreng Rappang Regency. The method of implementing this activity is a site survey, activity plan, activity implementation and activity evaluation. The results of the service showed an increase in participants' knowledge after counseling, one of which was in the good category, which increased from 32, 43% to 72,97%. This PKM activity was carried out at the Cendrana Village Office which was attended by government officials, mothers with toddlers, cadres, community leaders in Cendana village. This activity was carried out in conjunction with free medical examinations carried out by students, then the lecturers carried out socialization of the Joint Movement to Recognize, Prevent and Overcome Stunting Through Community Education. The consistency of the academic community in carrying out community service activities in the health sector needs to be maintained and even improved in order to support the tri dharma of higher education.